Microcirculatory disorders in patients with coronary heart disease and type 2 diabetes - Yu. N. Belenkov; E. V. Privalova; A. A. Shchendrygina; I. S. Chekneva; T. V. Emelyanova (Сеченовский вестник)
In patients with coronary artery disease (CAD) and those who suffer from second type diabetes mellitus micro vascular disorders was found. Diabetes is associated with an increased risk of cardiovascular events. It might be due to micro vascular changes. We hypothesized that patients with CAD and CAD with diabetes mellitus (CAD DM) have differences in structural and functional condition of microcirculation. We studied 50 patients with CAD, 43 CAD DM patients and 34 healthy controls. Digital photoplethysmography, computer nail fold videocapillaroscopy at baseline, after postocclusive hyperemia and during venous congestion were performed. We evaluated functional (occlusion index (IO)) and structural disorders (refl ection index (RI,%) of arterioles. The structure of coetaneous capillaries by capillary density (CD, cap/mm2) was assessed. Capillary function was estimated by percent perused capillaries (pPC,%). CAD and CAD DM patients had structural and functional changes of microcirculation. RI, IO and pPC in CAD and CAD DM patients were significantly different from controls (p<0.05), but there was no difference between CAD and CAD DM groups (p>0.6). CD in CAD DM group was significantly lower than in CAD and control groups (p< 0.019). The results show a decrease of micro vascular function in both CAD and CAD DM patients. CAD DM patients have also structural changes in capillary level.